Ajaran Etis Tujuan Hukum - Endy Purwanto; Marsudi Dedi Putra (Syntax Idea)
Ethical teachings in principle emphasize that law only aims to achieve justice. In Indonesia, justice is the ideal and goal to be achieved. However, the issue of justice still has not found its relevance. This article explains more deeply the ethical teachings of legal objectives and seeks their relevance to social justice in Indonesia. Normative juridical is this type of research with a statutory and historical approach. Qualitative descriptive is used as analysis. This research produces: (1) the parameters of justice are not single, starting from state political regulations to resistance to arbitrariness; (2) the relevance of ethical teachings to social justice finds its anchor point in the existence of equal opportunities before the law and government without exception for Indonesian citizens.